Pengaplikasian Media Pembelajaran Kotak Suara Pemilihan Umum Untuk Meningkatkan Minat Belajar Siswa di SMPN 5 Karawang Barat - ena (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2022)
Learning media is a means of communication for a teacher in conveying learning material, and is something that needs to be considered by the teacher. This is because through interesting and creative learning media it will stimulate students' interest in learning so that students will take part in learning enthusiastically. The purpose of this research is to attract student learning interest in the Civics learning process in class by using a new learning media, namely through the general election ballot box on the material Sovereignty of the Unitary State of the Republic of Indonesia and collaborating with subject teachers. The researcher uses a qualitative descriptive research method, which is a research method that describes the condition of objects in a real and natural way. In this study, the learning media of the general election ballot box as an independent variable binds to the variable of student learning interest. Data collection techniques were carried out in the form of direct observation in class, interviews with teachers and students and giving questionnaires to students. The results showed that class IX students tended to be active and able to receive learning material well on the subject of Sovereignty of the Unitary State of the Republic of Indonesia by implementing general election simulations. The purpose of this general election simulation is for students to understand the actual material, not only knowing the material but by practicing it directly to provide a clearer understanding of the material being taught